A Study of Dominant Female Figures in Fitzgerald's Writing: A Review: Exploring Fitzgerald's Portrayal of Dominant Female Characters and their Perception in American Classrooms (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Fitzgerald utilizes the language verbally expressed by his female characters to remain against a man centric portrayal. He utilizes the expository spaces that are commonly ascribed to being feminine or domestic to investigate and uncover their enemy of domineering development. On a surface read, the novel gives off an impression of being fortifying the male centric messages that we know about women are mothers, homemakers, followers of the men in their lives. Furthermore, the explanatory space wherein most perusers first experience and collaborate with this content is the classroom. The Great Gatsby is a novel that most, if not nearly all, American youngsters experience perusing and talking about in their high school English class. Therefore, how the novel is instructed greatly influences the translation and view of the talk encompassing this novel. A more profound understanding of these female characters has not converted into the expository space of the classroom. In the wake of investigating these parts of Fitzgerald's book, I will talk about how the comprehension of these female characters is formed inside American culture through the classroom, and how the ways this novel is instructed really keeps running contrary to how Fitzgerald really composes the females of this novel.